Sistem Informasi Akuntansi Penjualan Dan Pembelian - Dahlia Dahlia; Endah Puji Astuti; Endah Wiji Lestari; Anisa Rahmawati; Dea Rahmayani Nurendah (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2021)
Kata kunci: Sistem Informasi, Penjualan dan Pembelian Pada Koperasi Insan Mandiri. Abstract: The existing system in the Mandiri Insan Cooperative is a sales system that has problems that arise, one of which is a decrease in turnover/profits, a gradual lack of product sales levels due to the length of products sold, etc. Methods of data collection using interviews, direct observation, and observation. The results showed that the Mandiri Insan Cooperative still uses the sales and purchase accounting information system manually. Documents used in the sales accounting information system are sales notes, and lists of goods, while for purchases are sales invoices. Sales accounting information system procedures include the presentation of orders, receipt of payments and recording. Whereas for purchases are order recording, ordering, order processing, order receipt and order payment processing. The computerized sales and purchase accounting information system at the Mandiri Insan Cooperative is based on the WATERFALL analysis method, the new system provides greater benefits than the manual system. The design of the sales and purchase system is supported by the use of Unified Modeling Language (UML) as a system tool, programming language using Java Swing, and MySQL database. The results of the implementation after testing the system that has been running on the Insan Mandiri Cooperative, the sales and purchasing system at the Insan Mandiri cooperative runs smoothly, stable and efficiently by using a computerized system using Java Neatbeans Programming to implement it into the Sales and Purchase System at the Insan Mandiri Cooperative. Keywords: Accounting Information Systems, Sales and Purchase at the Insan Mandiri Cooperative.